2019
DOI: 10.1002/advs.201802104
|View full text |Cite|
|
Sign up to set email alerts
|

Spheroid Culture of Mesenchymal Stromal Cells Results in Morphorheological Properties Appropriate for Improved Microcirculation

Abstract: Human bone marrow mesenchymal stromal cells (MSCs) are used in clinical trials for the treatment of systemic inflammatory diseases due to their regenerative and immunomodulatory properties. However, intravenous administration of MSCs is hampered by cell trapping within the pulmonary capillary networks. Here, it is hypothesized that traditional 2D plastic‐adherent cell expansion fails to result in appropriate morphorheological properties required for successful cell circulation. To address this issue, a method … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 58 publications
2
19
0
Order By: Relevance
“…[45,46] It has been reported that cells isolated through spheroid dissociation exhibit greater therapeutic effect when transplanted in vivo since cells with a smaller size may increase microcirculation following transplantation. [47] In addition, cells from within the MSC spheroids produce a greater level of exosomes than 2D cultured cells due to their more round morphology of cells inside the spheroid. [48]…”
Section: Properties Of Spheroidsmentioning
confidence: 99%
“…[45,46] It has been reported that cells isolated through spheroid dissociation exhibit greater therapeutic effect when transplanted in vivo since cells with a smaller size may increase microcirculation following transplantation. [47] In addition, cells from within the MSC spheroids produce a greater level of exosomes than 2D cultured cells due to their more round morphology of cells inside the spheroid. [48]…”
Section: Properties Of Spheroidsmentioning
confidence: 99%
“…Inevitably, there are still several limitations to our study. Firstly, our findings were obtained using two-dimensional (2D) monolayer cell cultures, which do not adequately mimic the in vivo microenvironment exposed to GCs and present important limitations, such as reduced cell growth rates, cellular senescence, and low differentiation efficiency of MSCs ( Wang et al, 2009 ; Tietze et al, 2019 ). In recent years, three-dimensional (3D) culture systems have been developed and exhibit multiple advantages, such as mimicking the native 3D environment, facilitating the interaction and communication between cells, increasing extracellular matrix (ECM) secretion, and potentiating osteogenic differentiation of MSCs ( Zhang et al, 2015 ; Park et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since the knowledge about molecular mechanisms controlling cell mechanics is still limited, sorting for the stiff or soft fraction of cells and performing genomic, transcriptomic, or proteomic analysis could foster identification of cell mechanics regulators and elucidate target molecules for on-demand modification of cell stiffness. In case of clinical applications, enrichment of small and deformable cells, which were shown to have improved capability of passing the microvasculature 40 , could aid in attaining successful delivery of cells to target organs in cell-based therapies with, for example, hematopoietic stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…Raman scattering, for example, provides multiplexed information on the presence of chemical species in cells 28,29 , quantitative phase imaging yields internal mass density distributions [30][31][32][33] , and Brillouin scattering 34,35 and deformability cytometry 36 are used for mechanical phenotyping of cells. The latter is particularly relevant to feel for functional changes of cells involving cytoskeletal adaptations 37,38 or to identify disease states in blood 39 and can analyze cells in the context of cell circulation and migration ability 40 . One recent implementation of deformability cytometry, which is based on imaging cells flowed through a narrow constriction channel, analyzes the ensuing cell deformation continuously in real-time at rates of 100-1,000 cells/sec 41 , and is thus well-suited for downstream sorting.…”
Section: Introductionmentioning
confidence: 99%